2015
DOI: 10.1080/15548627.2015.1009795
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis challenges the connection between autophagy and senescence induced by DNA damage

Abstract: Abbreviations: 3MA, 3-methyladenine; AO, acridine orange; BafA1, bafilomycin A 1 ; CDKN1A/p21, cyclin-dependent kinase inhibitor 1A (p21, Cip1); cP1-4, cellular population 1 to 4; CPD, cumulative population doubling; DDR, DNA damage response; DFM, drug-free medium; H2AFX, H2A histone family, member X; MAP1LC3A/LC3, microtubule-associated protein 1 light chain 3 a; MTOR, mechanistic target of rapamycin; MTORC1, MTOR complex 1; NA, nuclear area; NMA, nuclear morphometric analysis; nP1-5, nuclear population 1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 73 publications
2
50
0
Order By: Relevance
“…We and others have previously shown that TMZ induces autophagy in several cell lines, including U-87 MG glioma cells (Filippi-Chiela et al, 2013;Natsumeda et al, 2011;Katayama et al, 2007) and induces cell enlargement (Filippi-Chiela et al, 2015). Autophagy induction was confirmed through a GFP-LC3 puncta formation assay (Fig.…”
Section: R/gfir Is Key For Measuring Avos By Flow Cytometrymentioning
confidence: 86%
“…We and others have previously shown that TMZ induces autophagy in several cell lines, including U-87 MG glioma cells (Filippi-Chiela et al, 2013;Natsumeda et al, 2011;Katayama et al, 2007) and induces cell enlargement (Filippi-Chiela et al, 2015). Autophagy induction was confirmed through a GFP-LC3 puncta formation assay (Fig.…”
Section: R/gfir Is Key For Measuring Avos By Flow Cytometrymentioning
confidence: 86%
“…The relationship between autophagy and senescence is still debatable. While the induction of senescence has been reported to be, at least in part, dependent on autophagy [31, 48], other studies concluded that senescence is independent of autophagy [6566]. Despite the close correspondence between autophagy and senescence in parental and Ligase IV−/− HCT116 cells, pharmacological and genetic inhibition of autophagy did not seem to affect the promotion of senescence even at high doses of radiation, indicating that promotion of senescence is independent of autophagy in this experimental model.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the autophagy inhibitor chloroquine has been shown to impair DNA damage repair and to increase the cytotoxic effect of the chemotherapeutic agent carboplatin in breast cancer stem cells (Liang et al, 2016). Accumulating evidence indicates that autophagy is exploited by tumor cells to resist radiation or chemotherapy-induced cell death and that genetic or pharmacological inhibition of autophagy sensitizes malignant cells to genotoxic therapy both in vitro and in experimental mouse models (Amaravadi et al, 2007; Pan et al, 2011; Chittaranjan et al, 2014; Wang and Wu, 2014; Filippi-Chiela et al, 2015; Liang et al, 2016; Piya et al, 2016). In line with this is the presence of autophagic vacuoles in Saos2 cells ( Figure 2 ), a p53 null human osteosarcoma cell line, which after prolonged expression of p21 WAF1/Cip1 exhibit enhanced aggressiveness and chemoresistance by deregulating the replication licensing machinery causing replication stress and fuelling genomic instability (Galanos et al, 2016).…”
Section: Functional Outcomes Of the Ddr – Autophagy Axismentioning
confidence: 99%